A practical chemoenzymatic approach to the synthesis of 3-hydroxy metabolites of tibolone - P. Ferraboschi; D. Colombo; S. Reza Elahi (Tetrahedron: Asymmetry, 2002)
Stereoselective preparation of 3-hydroxy metabolites of tibolone is easily accomplished by diastereoselective Candida antarctica lipase b-catalyzed transformations of 3alpha- and 3-beta-alcohols or acetates mixtures in organic solvents, in suitable amounts for biological studies.